INNOVATION ECOSYSTEMS BASED ON CLUSTERS: INTEGRATION OF INDUSTRIAL ENTERPRISES INTO THE GLOBAL INNOVATION NETWORK (Marketing Journal, 2025)
The article explores the role of cluster -based innovation ecosystems as a mechanism for integrating industrial enterprises into the global innovation network. It focuses on the key processes through which clusters accelerate knowledge exchange, foster join t research and development, and enable access to international markets. The 173 paper highlights the advantages of clustering for enhancing competitiveness and innovation capacity, while also identifying challenges related to coordination, intra - cluster competition, and reliance on government support. International case studies, such as Silicon Valley and the German automotive cluster, illustrate the transformative potential of clusters in fostering industrial innovat ion and global integration.
Keywords: cluster; innovation ecosystem; industrial enterprise; global innovation network; technological development; knowledge exchange; multinational corporations; government support; international cooperation; integration